Impaired Glucocorticoid Receptor Dimerization Aggravates LPS-Induced Circulatory and Pulmonary Dysfunction - Wepler, Martin; Preuss, Jonathan M.; Merz, Tamara; Hartmann, Clair; Wachter, Ulrich; McCook, Oscar; Vogt, Josef; Kress, Sandra; Gröger, Michael; Fink, Marina; Scheuerle, Angelika; Möller, Peter; et al. (Frontiers in Immunology, 2020)
Background: Sepsis as an acute systemic inflammation syndrome is the most common cause for acute lung injury (ALI). ALI induces acute respiratory failure leading to hypoxemia, which is often associated with multiple organ failure (MOF). During systemic inflammation, the hypothalamus-pituitary-adrenal axis (HPA) is activated and anti-inflammatory acting glucocorticoids (GCs) are released to overcome the inflammation. GCs activate the GC receptor (GR), which mediates its effects via a GR monomer or GR dimer. The detailed molecular mechanism of the GR in different inflammatory models and target genes that might be crucial for resolving inflammation is not completely identified. We previously observed that mice with attenuated GR dimerization (GRdim) had a higher mortality in a non-resuscitated lipopolysaccharide (LPS)- and cecal ligation and puncture (CLP)-induced inflammation model and are refractory to exogenous GCs to ameliorate ALI during inflammation. Therefore, we hypothesized that impaired murine GR dimerization (GRdim) would further impair organ function in LPS-induced systemic inflammation under human like intensive care management and investigated genes that are crucial for lung function in this setup. Methods: Anesthetized GRdim and wildtype (GR+/+) mice were challenged with LPS (10mg·kg-1, intraperitoneal) and underwent intensive care management (“lung-protective” mechanical ventilation, crystalloids, and norepinephrine) for six hours. Lung mechanics and gas exchange were assessed together with systemic hemodynamics, acid-base status, and mitochondrial oxygen consumption (JO2). Western blots, immunohistochemistry, and real time quantitative polymerase chain reaction were performed to analyze lung tissue and inflammatory mediators were analyzed in plasma and lung tissue. Results: When animals were challenged with LPS and subsequently resuscitated under intensive care treatment, GRdim mice had a higher mortality compared to GR+/+ mice, induced by an increased need of norepinephrine to achieve hemodynamic targets. After challenge with LPS, GRdim mice also displayed an aggravated ALI shown by a more pronounced impairment of gas exchange, lung mechanics and increased osteopontin (Opn) expression in lung tissue. Conclusion: Impairment of GR dimerization aggravates systemic hypotension and impairs lung function during LPS-induced endotoxic shock in mice. We demonstrate that the GR dimer is an important mediator of hemodynamic stability and lung function, possibly through regulation of Opn, during LPS-induced systemic inflammation.